Asbestos and ovarian cancer: examining the historical evidence. Issue 1 (January 2021) - Slomovitz, Brian; de Haydu, Christopher; Taub, Michael; Coleman, Robert L; Monk, Bradley J
Abstract : N/A: Asbestos recently returned to the spotlight when Johnson & Johnson halted sales of baby powder due to lawsuits claiming that the talc in baby powder may have been contaminated with asbestos, which has been linked to the risk of ovarian cancer development. Although talc and asbestos have some structural similarities, only asbestos is considered causally associated with ovarian cancer by the WHO's International Agency for Research on Cancer. While it is useful to understand the types and properties of asbestos and its oncologic biology, the history of its association with ovarian cancer is largely based on retrospective observational studies in women working in high asbestos exposure environments. In reviewing the literature, it is critical to understand the distinction between associative risk and causality, and to examine the strength of association in the context of how the diagnosis of ovarian cancer is made and how the disease should be distinguished from a similar appearing but unrelated neoplasm, malignant mesothelioma. Based on contextual misinterpretation of these factors, it is imperative to question the International Agency for Research on Cancer's assertion that asbestos has a clear causal inference to ovarian cancer. This has important clinical implications in the way patients are conceivably counseled and provides motivation to continue research to improve the understanding of the association between asbestos and ovarian cancer.